Wideband passive source localization. (5th July 2017) - Cheney, Margaret; Given, James A
Abstract: This paper develops a mathematical method for determining the locations of multiple transmitters from passive measurements of the signals at two or more receivers. The method applies to the case of emitters transmitting either wideband or narrowband signals.